Reputation economy: a new research paradigm for economic growth of territories - Grunichev, Alexander S.; Safiullin, Marat R. (Opción, 2019)
This paper is partially addressed at analyzing key approaches in the economic theory to studying reputation and its impact on the parameters of the socio-economic development of economic agents. In the paper, a system of concepts is developed with the basic classification of methods for quantifying reputation both at the micro and macro levels. As a result, the reputation economy is focused primarily on improving the competitiveness of business entities, besides finding rational economic models for the functioning of economic agents. In conclusion, only a small part of the problems of studying the reputation economy is touched upon.